Factors Affecting Qom Medical School Students' Intention regarding Organ Donation: a Study based on Behavioral Intention Model - Saimak Mohebi; Masomeh Mohammadi-zavareh; Fatemeh Zamani; Zabihollah Gharlipor; Hosein Heidary (Mashhad University of Medical Sciences, 2016)
Background and objective: Today, organ donation and transplantation play a critical role in saving patients with the advanced deficiencies of body organs. In the meantime, organ donation is influenced by a variety of cultural, social, and religious factors. They have an impact on individuals' intention (tendency) to donate organs after brain death. This study examined factors affecting Qom Medical School students' intention regarding organ donation. The examination was carried out based on behavioral intention model.  Methods: This cross-sectional study was conducted on 304 medical students. They were selected by multiple-stage sampling technique from Qom Medical School. The research data was collected by a validated reliable questionnaire. It comprised questions regarding personal specifications, awareness, attitude, abstract norms, and intention. The collected data was analyzed by SPSS 18. Results were described by central statistical indices and analyzed using independent sample T-test, Pearson correlation coefficient, and linear regression (P